Differentiation of the body build in taekwondo-ITF competitors of the men`s Polish national team and direct base athletes - Jagiello, W. (Archives of Budo, 2015)
Background and Study Aim: Body build of competitors of those combat sports where there is a breakdown into weight categories still provides substantial information on the effects of long-term training of people who have gone through stages of selection for the given sport. Yet, in fact, there is still a lack of scientific knowledge about the morphofunctional potential of persons (mainly children and adolescents) who became interested in particular combat sports. The purpose of the study is knowledge of the properties of body composition of taekwondo-ITF competitors from the national team in comparison to members of the same population not professionally engaged in sport. Material and Methods: The study involved 21 taekwondo-ITF athletes. The subjects` age was 18.5-32.2 years (x 24.5 ±4.1), body weight 62.7-100 kg (x75.3 ±10.3), body height 167.0-195 cm (x179.64 ±8.33). Their training experience was 8.42-22.42 years (x13.62 ±3.37) and was significantly diversified (V% = 24.76). The examined persons represented four weight categories: light-weight, middle-weight, heavy-weight, and hyper-weight one. The reference group was made of students of Warsaw University of Technology (Poland). Twenty basic somatic features were measured. The following indices were calculated: slenderness, BMI, Rohrer`s, Manouvrier`s, shoulder-pelvis. Body density, total body fat, active tissue, the general profile of body composition, and internal proportions of body composition were determined. Results: Weight categories are an important factor in determining the morphological diversity of taekwondo-ITF competitors. A characteristic feature of their body composition is extremely low contribution of fat in all weight classes with a simultaneous significance of the length factor in the heavy-weight and the hyper-weight category and the stoutness one in the light-weight and the middle-weight category. Conclusions: The choice of an appropriate combat technique (hits with extremities and a combination of these elements of combat) for the body composition and other components of a taekwon-do athlete`s personality will remain a constantly open problem. These problems must be solved by coaches with reference to specific athletes on an individual basis.